Structural and Physicochemical Properties of a Polymerizable Surfactant Synthesized from N-Methylol Acrylamide - Tamer, Yasemin; Yamak, Hale Berber; Yildirim, Huseyin (SPRINGER HEIDELBERG, 2016)
A new polymerizable nonionic surfactant with reactive vinyl groups has been synthesized from N-methylol acrylamide using a two-step procedure. The structure of the surfactant molecule was characterized by Fourier transform infrared, H-1 nuclear magnetic resonance and mass spectroscopy. The surface active properties alongside its self-assembly properties were investigated by surface tension, electrical conductivity, and fluorescence spectroscopy measurements. As compared with other nonionic surfactants, this study showed that this polymerizable surfactant possesses slightly a higher critical micelle concentration (CMC) value and the surface tension value at CMC. The obtained CMC values were compatible among measurements, ca. 0.02-0.038 M. The evidence of micelle formation also provided by the zeta potential measurements and the obtained zeta potential values showed that the polymerizable surfactant solutions had limited stability. The hydrolysis stability and solubility of the polymerizable surfactant were also investigated. The solubility results have shown that it was soluble in polar solvents while insoluble in nonpolar solvents both at room temperature and 40 degrees C. The acidic and basic hydrolysis of the surfactant increased as the temperature increased and the hydrolysis stability was 180 min (basic medium) and 55 min (acidic medium) at 80 degrees C.
Keywords: Polymerizable nonionic surfactant; N-methylol acrylamide; Critical micelle concentration (CMC); Physicochemical properties; Surface tension; CRITICAL MICELLE CONCENTRATION; FREE-RADICAL POLYMERIZATION; EMULSION POLYMERIZATION; REACTIVE SURFACTANTS; HETEROPHASE POLYMERIZATION; CROSS-LINKING; NONIONIC SURFACTANTS; CONCENTRATION CMC; SURFMERS; PERFORMANCE; Chemistry; Engineering